2019
DOI: 10.9771/cmbio.v18i1.29313
|View full text |Cite
|
Sign up to set email alerts
|

Alfa no estado alterado de consciência: meditação raja yoga

Abstract: <p><strong>Introdução:</strong> A meditação é uma técnica ancestral praticada por tradições religiosas e não religiosas, para alcançar benefícios espirituais e na saúde. É considerada um dos estados alterados de consciência. Estudos com ressonância magnética funcional e eletroencefalografia revelaram que existe diminuição da atividade cerebral no lóbulo parietal superior, durante a meditação. Na meditação, a frequência alfa aumenta no córtex cerebral quando comparada ao relaxamento e é caract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…On the other hand, considering that chronic pain presents a high prevalence in the Brazilian population 43 , using treatment strategies that are supported by the literature for chronic pain and that also seem to increase the activity of Alpha waves seems to be a safe path. Among these strategies, it's possible to mention neurofeedback training 44 , exercises 45 , meditation 46 , and myofascial manual techniques 47 . The hypothesis of the relationship between the brain electrical pattern and pain becomes stronger when it was found that part of these interventions can be found in pain treatment guidelines 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, considering that chronic pain presents a high prevalence in the Brazilian population 43 , using treatment strategies that are supported by the literature for chronic pain and that also seem to increase the activity of Alpha waves seems to be a safe path. Among these strategies, it's possible to mention neurofeedback training 44 , exercises 45 , meditation 46 , and myofascial manual techniques 47 . The hypothesis of the relationship between the brain electrical pattern and pain becomes stronger when it was found that part of these interventions can be found in pain treatment guidelines 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Raja yoga is one of the oldest systems of yoga and has been a well-known practice in India for millennia. It proposes building the spiritual world without requiring prior faith or belief (Vivekananda 2009;Agarwal et al 2020), thus being accessible to people of all ages and contexts, without rituals or mantras, and can be practiced anywhere and at any time (Toutain et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Yoga is a practice used to silence the agitated mind and focus on positive thoughts to direct the mind's flow and fill the being with an inner stillness (Vivekananda 2009). Therefore, the aim is to obtain a moment for reflection and silence, away from the hustle and bustle of everyday life that often leads the individual to experience stress and, consequently, to develop mental, emotional, and physical imbalances (Toutain et al 2019). The practice of yoga is structured in eight steps: (1) Yama, which consists of self-restraints (non-violence, truthfulness, non-stealing, control of the senses, and non-acceptance of gifts); (2) Niyama, which consists of religious observances (cleanliness, contentment, austerity, self-study, and surrender to God's will); (3) Asana, or yoga posture; (4) Pranayama, or control of prana (breathing exercises); (5) Pratyahara, or withdrawal of senses from objects; (6) Dharana, or progression in concentration; (7) Dhyana, or meditation; and (8) Samadhi, or achieving a superconscious state (Prabhavananda;Patanjali.…”
Section: Introductionmentioning
confidence: 99%
“…Estudo realizado no ano de 2018 relata que trabalhos que utilizam o eletroencefalograma (EEG) e que examinam a neurofisiologia das técnicas de meditação, evidenciaram mudanças consistentes nas potências das ondas teta e alfa [4] . A potência destas últimas ondas aumenta durante a meditação e tarefas que requerem atenção sustentada [5] .…”
Section: Introductionunclassified